(untitled) (Bangladesh Journal of Radiology and Imaging, 2026)
Background: Renal cell carcinoma is the commonest renal malignancy worldwide. CT scan is a useful imaging modality to diagnose renal cell carcinoma. Objective: The study aims to evaluate diagnostic performance of Computed Tomography scan in the diagnosis of Renal cell carcinoma. Methods: This cross sectional study was conducted in the department of Radiology and Imaging of Dhaka Medical College and Hospital from July 2018 to June 2020. A total of 48 patients were included in the study after taking informed written consent. Detailed history was taken and thorough clinical examination were performed along with CT scan imaging and histopathological examination. Results: The mean age was 64.43+10.72 years with range from 32 to 73 years. Male to female ratio was 1.53:1. Majority of the patients had hematuria (54.16%), malaise (56.25%) and anemia. Majority (58.3%) patient had lesions d”4cm and 20(41.7%) patients had lesion size more than 4cm. Majority of the patients had hypodense lesions (54.1%) followed by isodense (41.6%) and hyperdense lesions (2.08%). Regarding CT diagnosis, 89.6% patient had RCC, 4.16% patients had TCC, 2.1% patient had lymphoma, 2.1% patient had oncocytoma and 2.1% patient had suprarenal gland adenoma. Regarding histopathological diagnosis, 87.55 patients had RCC, 4.16% patients had oncocytoma, 2.1% patient had lymphoma, 2.1% patient had TCC and 2.1% patient had suprarenal gland adenoma. CT scan showed a sensitivity, specificity, accuracy, PPV and NPV of 97.6%, 66.7%, 93.7%, 95.3% and 80% respectively in the evaluation of RCC. Conclusion: This study concludes that CT scan is a useful diagnostic modality in evaluation of renal cell carcinoma. BJRI, 2024; VOL. 32(2): 90-98